0702 Real World Characteristics of Central Sleep Apnea: Experience at One Academic Medical Center. (25th May 2022) - An, Liudan; Genuardi, Michael; Fudim, Marat; Lund, Lars; Mehra, Reena; McKane, Scott; Meyer, Timothy; DeSensi, Rebecca; Patel, Sanjay
Abstract: Introduction: Despite growing recognition of sleep disordered breathing, the prevalence and clinical characteristics of central sleep apnea (CSA) in real-world sleep referral populations remain poorly understood. We used historical data from the University of Pittsburgh Medical Center (UPMC) to assess the differences in patients with CSA compared to obstructive sleep apnea (OSA). Methods: We retrospectively reviewed the medical records of 29, 803 patients who underwent in-lab diagnostic polysomnography at six UPMC sleep labs between 2004 and 2018. Baseline clinical characteristics and polysomnography results including apnea hypopnea index (AHI), central apnea index (CAI), and obstructive apnea index (OAI) were extracted from the electronic health record. Among those with AHI≥5, patients were categorized as CSA if CAI≥5 and CAI>OAI or OSA if OAI≥5 and OAI>CAI. Results: CSA and OSA were identified in 2% (583/29, 803) and 34% (10, 090/29, 803) of patients, respectively, while 32% had AHI≥5 but didn't meet either CSA or OSA criteria (CAI and OAI<5 or CAI=OAI) and the remaining 32% had AHI<5. Median AHI was 41 events/hr for CSA vs. 36 events/hr for OSA (p<0.01). The median percentage of apneas being central was 78% for CSA vs. 0% for OSA (p<0.01). Compared to patients with OSA, those with CSA were more likely to be male (78% vs. 66%), older (58 vs. 54 yrs), have lower body mass index (32 vs. 35 kg/m2), have heart failure (23% vs. 13%), atrial fibrillation (19% vs. 8%), stroke (5% vs. 2%), myocardial infarction (7% vs. 2%), diabetes (27% vs. 22%) and have received a prescription for methadone (1.5% vs. 0.3%) [all p<0.01]. In multivariable logistic regression, all factors except stroke remained independently associated with CSA. The strongest predictors of CSA (compared to OSA) were methadone prescription (adjusted odds ratio=4.9, 95% CI [2.3-10.6]) and myocardial infarction (1.9, [1.3-2.8]). In contrast, the prevalence of CSA and OSA were similar across races. Conclusion: CSA was identified in 2% of patients undergoing polysomnography in everyday clinical practice and independently associated with a variety of clinical characteristics. Recognition of characteristics associated with CSA can lead to more targeted screening and treatment in a broader population beyond just heart failure patients. Support (If Any): ZOLL Respicardia, Inc.